Water impacts nutrient dose responses genome-wide to affect crop production - Joseph Swift (Nature Portfolio, 2019)
Scarcity of water and nutrients limit crop yields. Here Swift et al. show that gene expression in rice responds differently to changes in the absolute amount of nitrogen available compared to nitrogen concentration and identify expression profiles associated with crop performance in arid, low-nutrient soils.